Pembelajaran Berdiferensiasi Berbasis Sains Lokal Untuk Mendorong Literasi Digital - Darmayanti, Nyoman Sri; Yuliani, Ni Made (Jayapangus Press, 2025)
Learning by using cellphone cannot be separated so it is vulnerable to hoax news, including science hoaxes. So far, learning has not integrated activities that encourage digital literacy so that students can deal with hoax news, especially science hoaxes. In fact, one of the principles of differentiated learning is a quality curriculum. For this reason, differentiated learning based on local science issues is implemented to encourage students' digital literacy. Objective best practice This is to describe the success of achieving learning objectives and digital literacy in local science-based science differentiation learning. Differentiated learning is carried out by differentiating content according to the learning styles displayed in it google site Sains with Heart. Differentiation of the process with critical analysis of local science issues according to student interests. Product differentiation with the freedom to present the results of the analysis orally in class and in writing on a digital portfolio on Padlet. The results of this learning were successful in encouraging the achievement of students' learning goals. The results obtained were 33.3% of students (11 people) got a score in the Very Good category (A) and 66.7% (22 people) got a good category (B). The average achievement of all students is 83.8. Apart from that, it has also succeeded in encouraging students' digital literacy. The results obtained were 12.1% of students (4 people) in the very good digital literacy category (A), 78.8% (26 people) in the good digital literacy category (B) and 9.1% (3 people) in the sufficient digital literacy category. The average achievement of all students is 81.1 (good category).